2020
DOI: 10.37194/jpmb.v2i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Perusahaan, Volume Perdagangan Saham, Volatilitas Return Saham, dan Dividend Yield terhadap Bid-Ask Spread

Abstract: Bid-Ask Spread sebenarnya mengukur informasi tidak simetris atau asymmetric information antara broker dan investor. Besar kecilnya Bid-Ask Spread menunjukkan seberapa besar asymmetric information diantara pelaku pasar. Untuk mengurangi tingkat asymmetric information tersebut maka pelaku pasar berupaya mendapatkan sinyal tertentu yang dapat dijadikan sebagai informasi untuk mengurangi ketidakpastian yang terjadi. Penelitian bertujuan untuk menganalisis pengaruh Ukuran Perusahaan, Volume Perdagangan Saham Volati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The phenomenon of securities traded in the capital market can be detected from the transaction volume. The total quantity of securities traded during a specific period and the number of securities outstanding during that time are measured by volume activity (Rio et al, 2020). The large trading volume at the time of supply and demand for shares affects the tendency of the ups and downs of stock prices.…”
Section: Trading Volume Activitymentioning
confidence: 99%
“…The phenomenon of securities traded in the capital market can be detected from the transaction volume. The total quantity of securities traded during a specific period and the number of securities outstanding during that time are measured by volume activity (Rio et al, 2020). The large trading volume at the time of supply and demand for shares affects the tendency of the ups and downs of stock prices.…”
Section: Trading Volume Activitymentioning
confidence: 99%
“…The bid-ask spread actually measures asymmetric information or asymmetric information between brokers and investors. Therefore, the bid-ask spread is very important to obtain information about asymmetric information in the capital market (Rio et al, 2020).…”
Section: Preliminarymentioning
confidence: 99%
“…Table1.649 and the value of Prob. 0.5268 > 0.05, it can be concluded that Ha is rejected, so it can be concluded that the Stock Return Volatility variable in this study has no effect on the Bid-Ask Spread.According to Husnan inRio et al (2020), an efficient investment is one that provides a certain risk with the greatest rate of return, or the highest level of return with the smallest risk. In other words, if there are two investment proposals that provide the same level of profit, but have different risks, a rational investor will choose an investment that has a smaller risk.…”
mentioning
confidence: 99%
“…Tingginya harga saham menunjukkan semakin kuatnya persaingan diantara para pelaku pasar. Ketatnya persaingan berpengaruh terhadap harga beli (bid) yang relatif naik dan harga jual (ask) yang relatif turun sehingga menyebabkan spread akan menyempit Volume perdagangan merupakan rasio dari keseluruhan lembar saham yang diperjual belikan pada suatu waktu dibandingkan dengan keseluruhan saham yang beredar waktu tersebut (Rio, Husnatarina and Oktavia, 2020). Investor lebih tertarik dengan saham yang memiliki return yang cukup tinggi meski mempunyai resiko.…”
Section: Pendahuluanunclassified